DEVELOPING MUSICAL-AESTHETIC TASTE IN YOUNG LEARNERS: METHODOLOGIES AND INNOVATIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This study addresses the development of musical-aesthetic taste in students attending piano classes at children’s music and art schools. The research emphasizes the importance of integrating innovative pedagogical technologies and interactive methods into modern music education. Analysis of theoretical and methodological sources highlights the need to move beyond mechanical performance towards meaningful, expressive interpretation. Practical methods aimed at enhancing students’ musical thinking, aesthetic perception, and performance skills are presented. These approaches provide guidance for music educators on how to foster artistic sensitivity and develop a conscious appreciation of both national and global musical heritage in young learners.